Assessment of postoperative risk factors for EEG abnormalities in routine clinical management after paediatric cardiopulmonary bypass. (6th April 2021) - Li, Meng-Yao; Lou, Xiao-Bin; Cui, Yan-Qin; Lin, Rou-Yi; Ning, Shu-Yao; Li, Li-Juan; Li, Jian-Bin; Huang, Guo-Dong; Zou, Ming-Hui; Ma, Li; Chen, Xin-Xin; Li, Jia
Abstract: OBJECTIVES: The postoperative risk factors for electroencephalogram(EEG) abnormalities after paediatric cardiopulmonary bypass (CPB) remain to be identified. We investigated the characteristics of EEG abnormalities and risk factors in routine clinical management post-CPB. METHODS: EEG and cerebral oxygen saturation (ScO2 ) were monitored in 96 patients (aged 3 days, 37 months, median 5 months) for 72 h post-CPB. Clinical measurements included 4-hourly arterial and central venous pressure, arterial blood gases, doses of inotropic and vasoactive drugs, daily C-reactive protein (CRP) and NT-proB-type Natriuretic Peptide (NT-proBNP). Demographics, STAT categories and outcomes (duration of mechanical ventilation, CICU stay) were recorded. Un RESULTS: Seizures occurred in 20 patients (20.8%) beginning at 0–48 hand lasting 10 min–31 h; background abnormalities occurred in 67 (69.8%) beginning at 0–8 h and lasting 4–48 h. Patients with EEG abnormalities had worse outcomes. In univariable regression, seizures positively correlated with STAT categories, CPB time, temperature, blood pressure, central venous pressure, NT-proBNP, CRP, lactate and epinephrine, negatively with ScO2 and PaCO2 ( P < 0.001 for lactate and epinephrine, P < 0.1 for the remaining). The degree of background abnormalities positively correlated with STAT categories, CPB time, operative time, central venous pressure, milrinone, negatively with blood pressure ( P = 0.0003–0.087); it negatively correlated with lower dose of epinephrine ( P < 0.001) and positively with higher dose ( P = 0.03l). In multivariable regression, seizures positively correlated with epinephrine, lactate and temperature; the background abnormality correlations remain significant except for milrinone and operative time ( P < 0.001 for epinephrine, P < 0.05 for the remaining). CONCLUSIONS: Numerous perioperative risk factors are associated with EEG abnormalities post-CPB. The most significant and consistent risk factor is epinephrine.